Effect of soil amelioration on high value vegetables grown under protected conditions - VERMA, VEERENDRA KUMAR; CHOUDHURY, B U; JHA, ANJANI KUMAR (The Indian Journal of Agricultural Sciences, 2022)
High-value vegetable production under open field in northeast India's hilly ecosystem often suffers from abiotic and biotic stresses (low temperature, soil acidity and moisture deficit during winter, and infestation of pests-diseases during humid summer). Protected cultivation with soil ameliorative measures may help in overcoming these limitations while sustaining year-round production. An experiment was conducted at the Horticulture Experimental Farm, ICAR Research Complex for NEH Region, Meghalaya for three consecutive years (2016–18) to study the yield performance of 4 high-value vegetables (tomato, capsicum, king-chilli and cucumber) grown under naturally ventilated polyhouse in the strong acid soils (pH